Student attendance system using blockchain technology - Nur Syafiqa Nabilah, Mohd Sanosi (2019)
Attendance is very important to every student. To make sure the student’s attendance is secure from other third parties, student’s attendance system using blockchain technology will be implement to FSKKP students. First problem statement of this system is Time-consuming process because traditional way of recording the attendance such as using attendance sheet will become a time-consuming process especially when there are more students. the second problem is Lack of security when attendance sheet can be less secure than electronic systems. The data is easy to lose because of the intervention of many parties. The attendance system also can be misused. The third problem statement is limitation of space because the old records of attendance sheet kept by the lecturer will take up space when the student has finished their studies or after the end of the semester. The of the objective has been identify in order to solve the problem statement issue. First one is, to prevent time consuming process for student’s attendance. Second one is, to develop a system for student’s attendance using blockchain technology. The last one is, to provided better security to this system.